Relationship between Population and Intensity of Cassava Mealybug (Phenacoccus manihoti) Attack on Flores Island - Yustina M S W Puu (Caraka Tani: Journal of Sustainable Agriculture, 2019)
This study was conducted to obtain population data and damage due to the attack of Phenacoccus manihoti Cassava mealybug pest on cassava plantations on Flores Island. This research was carried out in Ende Regency, Sikka Regency and Nagekeo Regency, East Nusa Tenggara Province (NTT). The research was conducted in October 2017. Method used in this research was descriptive method with direct observation and sampling. Cassava plants that were observed included plants that grew as fences, yard plants and those in farmers’ gardens with an area of ± 0.5 ha. The variables observed included population abundance and crop damage intensity in all locations of cassava plantations. The average population of Phenacoccus manihoti in each regencyis 131.12 individuals plant-1 in Sikka Regency, 36.95 individuals plant-1 in Nagekeo Regency and 6.4 individuals plant-1 in Ende Regency. Phenacoccus manihoti pest attack intensity in each observation location in the three Regencieson Flores Island is mild to moderate, namely 43.3% in Sikka Regency; 20% in Ende Regency and 22% in Nagekeo Regency. Damage intensity is influenced by cassava mealybug population 15% and other factors 85%.